BELA BELI KULON PROGO SEBAGAI SEBUAH MODEL ENDOGENOUS DEVELOPMENT - Indra Cahya Nugraha; Siti Fatimah; Belia Fransiska; Endriana Prasetyawati (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2022)
Regional inequality and poverty are common problems for almost every developing country. Yogyakarta Special Region is a region equal to a province with the highest regional inequality rate in Indonesia. Endogenous development can be a solution to address inequality and poverty, but only some regions that implement this method are prosperous. This research used qualitative description to elaborate the endogenous development model in the case of Kulon Progo Regency with analysis referring to elements of the endogenous development frame. Results showed that innovation and implementation of endogenous development in the Kulon Progo Regency called “Bela Beli Kulon Progo,” positively impacted poverty alleviation.